Interações fitoplâncton-bactéria: associações específicas e possíveis implicações ecológicas - Bagatini, Inessa Lacativa (Universidade Federal de São Carlos, 2013)
The occurrence of nuisance phytoplankton blooms is a worldwide problem that affects water quality and other aquatic biota. Bacterial (non-cyanobacterial) communities can influence and interfere with the formation, maintenance and termination of such blooms via many biotic interactions. The bacterial communities associated with 3 bloom forming phytoplankton species, the Cyanobacteria Microcystis aeruginosa and Cylindrospermopsis raciborskii and the diatom Aulacoseira granulata, were assessed by the 454-Pyrosequencing of 16S rRNA gene amplicons (V3-V5 regions). The aims of this work were to verify if different bacterial communities would develop with different host species, or in different fractions (attached and free-living bacteria) and different growth phases (physiological state) of each phytoplankton species. Still using pyrosequencing data, the strength of phytoplankton-bacteria association was analyzed for M. aeruginosa and A. granulata by culturing the phytoplankton species with different bacterial inocula (and growth medium for the cyanobacteria). Furthermore, the effects of bacterial strains isolated from attached community of A. granulata and M. aeruginosa cultures were tested on the growth of the phytoplankton species. Significantly different bacterial communities developed: i) in response to physiological state and between fractions of the same phytoplankton culture, and ii) in response to the different host phytoplankton species, with major differences in the proportion of the OTUs between phytoplankton cultures rather than in the absence or presence of specific bacterial taxa. Differences between experiments significantly changed the BCC that developed associated with the same host species. However, some bacterial OTUs were found associated with the same phytoplankton species in different experiments, suggesting a tight association with the host species. Most of the strains either isolated from M. aeruginosa or from A. granulata affected negatively the growth of the diatom. However, the isolated strains had no effect on the cyanobacterial growth, suggesting the importance of bacterial community to the dominance of M. aeruginosa on Barra Bonita Reservoir, at least concerning to the competition with A. granulata.
Interaction phytoplankton-bacteria: specific associations and possible ecological implications
Keywords: Ecologia microbiana; Cianobactéria; Interação algas-bactérias; Pirossequenciamento; Diatomáceas; Composição da comunidade bacteriana; CIENCIAS BIOLOGICAS::ECOLOGIA